Deep Learning Techniques for Adaptive Resource Allocation and Data Reliability in Cloud Ecosystems - Pentyala, Dillep Kumar (International Journal of Scientific Research and Management (IJSRM), 2024)
Cloud ecosystems are of particular importance in terms of providing supporting framework for a wide range of current and future digital services and applications, but they also have potentially fatal flaws in terms of resource management and data integrity. Indeed, conventional approaches are normally slow in meeting the needs of such surroundings in a way that results in wastage of resources, poor productivity and propensity to failure. This article envisages how the deep learning methods can be applied to these critical concerns. In this paper, with the aid of neural networks, reinforcement learning, and ensemble methods, we contribute adaptive approaches to managing the distribution of the resources while improving the credibility of the data in real-time. The features of the methodology include the use of the workload forecasting based on the predictive modeling, the dynamic resource management based on the reinforcement learning, and the usage of the data integrity and fault tolerance based on the anomaly detection algorithms.The result shows that deep learning is not only more accurate but also more scalable and flexible in a highly dynamic environment compared to the heuristic methods. A simulated analysis of the proposed scheme shows scenarios of decreased latency, more efficient load distribution, and increased system stability despite fluctuating conditions. That is why the experimental outcomes reported in this article evidence the goal of deep learning in cloud environments to construct a more robust and efficient infrastructure. They generalize far beyond the optimization of operational functionality and open up opportunities for cost reduction and increased sustainability in the field of cloud computing. The findings of this research underscore the need for continuing the enhancement of the AI integration into cloud systems for the purpose of managing new issues and realizing new possibilities.